2018
DOI: 10.1111/jace.16234
|View full text |Cite
|
Sign up to set email alerts
|

First printing of continuous fibers into ceramics

Abstract: This article reports a novel method for three‐dimensional (3D) printing of continuous fibers into ceramics to improve the mechanical properties of printed ceramics, which is difficult in other 3D printing technologies. The ceramics were derived by pyrolysis of thermoplastic ceramic precursor feedstocks, which were prepared by two methods. One is homogeneously mixing thermoplastic resins and ceramic precursors. The feedstocks prepared by this method exhibit good thermoplastic properties and can be extruded into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 45 publications
(59 reference statements)
0
13
1
2
Order By: Relevance
“…The mechanical properties of our continuous C f /SiC specimens are presented and compared to existing data in Table 1. Compared to the previously reported results on C f /SiC fabricated using additive manufacturing techniques, 4,9,[26][27][28] the strength and density of the C f /SiC composites manufactured in this work are considerably improved. The enhanced density is attributed to the high solid content of the SiC ink and the conversion of the PCS coating on the carbon fibers to SiC.…”
Section: Microstructure and Properties Of C F /Sic Compositescontrasting
confidence: 51%
See 1 more Smart Citation
“…The mechanical properties of our continuous C f /SiC specimens are presented and compared to existing data in Table 1. Compared to the previously reported results on C f /SiC fabricated using additive manufacturing techniques, 4,9,[26][27][28] the strength and density of the C f /SiC composites manufactured in this work are considerably improved. The enhanced density is attributed to the high solid content of the SiC ink and the conversion of the PCS coating on the carbon fibers to SiC.…”
Section: Microstructure and Properties Of C F /Sic Compositescontrasting
confidence: 51%
“…8 One study was reported on the manufacturing of continuous C f /SiC composites using a methylsilsesquioxane resin ink with a coaxial nozzle system that was designed for printing carbon fiber-reinforced polymer composites. 9 Due to the low solid contents of printing ink, most sintered ceramic matrices are loose. Gaps exist between the fibers and between the ceramic matrix and fibers.…”
Section: Introductionmentioning
confidence: 99%
“…。 本课题组开展了一系列 SiC 陶瓷 SLS 增材制造的研究。朱伟等人 [13] 采用溶剂蒸发 法制备了 C f 含量高达 70%(体积百分比)的酚醛树脂覆膜粉末,经 SLS 成形后的坯体的 体积密度、开孔率、抗弯强度分别可达 0.475 g/cm 3 , 68.89%和 5.13 MPa;傅华等人 [14] 在 上述材料体系中加入硅粉,从而在后续反应烧结中减少碳化后的连续碳相,以降低残硅 和残碳。通过溶剂蒸发法制备的 C f 覆膜粉末具有良好的铺展性和松装密度,以及优良 的 SLS 成形性。相比较而言,邹阳等人 [16] 为严重,难以铺展。但溶剂蒸发法制备 SLS 粉末的步骤较为繁琐,而机械混合法则较为 简单易行, 所以目前科研和生产中所使用的 SLS 专用 SiC 粉末的制备方法仍以机械混合 法为主,比如西安交通大学宋索成等人 [17] 通过在 SiC 微粉/环氧树脂体系中添加球状石 墨,以优化后续反应烧结过程,最终制得的 SiC 陶瓷抗弯强度最高可达 348 MPa。 相较于 SLS,3DP 成形不需要向粉末中添加有机黏结剂,该特点使得 3DP 专用 SiC 粉末的制备较为容易,仅需要考虑陶瓷粉末本身的铺展性能和松装密度,通过粉末颗粒 级配、喷雾干燥等方法即可得到流动性和松装密度均符合使用要求的粉末。以色列金属 研究所 Fleisher 等人 [18] 直接采用机械混合的 SiC/B 4 C 复合粉末完成了 SiC 陶瓷的 3DP 增 材制造,其中 B 4 C 充当反应过程中的助剂,可促进液相烧结,减少残硅量。西北工业大 学成来飞团队 [15][23] 采用球磨法制备了短切碳纤维固含量为 20.86%(体积百分比)的浆料, 表现出良好的 光固化成形性。 用于 DIW 的 SiC 陶瓷浆料/膏体的设计与制备可以更加灵活, 需要满足以下几点 [25] : (1)具有良好的剪切稀变行为,能够从喷头中顺利挤出不发生堵塞; (2)具有良好的 黏弹性,从喷头挤出后可快速固化保持形状; (3)固含量尽可能高,以减弱 SiC 坯体在 后续处理过程中的体积和形状变化。在进行 DIW 成形时,纤维、晶须或纳米线等通过 喷嘴挤出时展现出独特的取向性,从而使得最终制得的 SiC 陶瓷基复合材料具有良好的 力学性能。西安交通大学鲁中良团队 [24,26] 研究了 C f 在 DIW 过程中的取向行为,探究了 C f 的取向与喷嘴直径和剪切力之间的关系。 中南大学张斗团队 [27,28] 通过在 PCS 先驱体中 添加 SiC 微粉和 SiC w 用以调控 SiC 坯体的线性收缩,SiC w 在挤出过程中展现了良好的 取向性。 1.3 增材制造专用 SiC 丝材 SiC/树脂复合丝材的制备通常包括粉末干燥、混合球磨、挤出成丝这三步,然后便 可以用于 FDM 打印制备坯体,其中 SiC 的含量最高可达 60%(质量百分比) [29] 。FDM 丝 材制备过程较为繁琐, 固含量难以提高, 因此基于 FDM 制备 SiC 陶瓷的报道较少。 Baux 等人 [30] 直接采用聚乙烯醇/弹性体打印陶瓷坯体,再通过浸渍的方法引入 SiC 陶瓷先驱 体, 最终制得了 SiC 陶瓷, 该思路相较其他 SiC 的增材制造工艺而言, 并没有突出优势, 潜在应用价值难以发掘。值得注意的是,FDM 打印连续纤维复合材料备受关注,连续 纤维增强聚合物复合材料已经可以通过 FDM 稳定成形。西北工业大学梅辉等人 [31] 首先…”
Section: 至无法制备。增材制造(Additiveunclassified
“…DIW 又被称为自动注浆成形(Robocasting 或 Robotic deposition) ,浆料储存在料盒 中,在机械螺杆挤出或气压装置的压力下从喷嘴中挤出,层层堆叠构建三维实体 [52] 。 DIW 构筑模型的尺度已经可以由微观(10 -6 m)到宏观范围(1 m) [52~54] 。除了前面提 到的墨水性能,打印参数(压力、速度)和环境条件(温度、湿度)对坯体成形也有较 大影响。西安交通大学鲁中良团队 [24,26] 等人 [55] 以 SiC 胶体和硼聚碳硅烷(BPCS)陶瓷前驱体共混制备陶瓷浆料,通过 DIW 与 液相烧结制备 SiC 光学构件。 中南大学张斗团队 [27,28] 报道了 SiC 晶须/PCS 浆料的墨水直 写工艺,SiC 晶须在打印过程中高取向排列,具有良好的打印性。短碳纤维、SiC 晶须 和 SiC 纳米线在打印过程中的取向性为揭示了一种普遍的机制,即直写过程的剪切力驱 动纤维材料定向排列。DIW 制备的陶瓷精度较差、缺陷较多,因此精细复杂 SiC 构件的 DIW 成形较为困难。西安交通大学李涤尘、鲁中良团队 [56] 提出了一种 DIW 成形连续 C f 当前通过 FDM 成形的主要为陶瓷基复合材料 [29,57,58] 。值得注意的是,随着 FDM 打印连 续纤维增强聚合物复合材料的兴起,人们渐渐发现了连续纤维增强 SiC 陶瓷的潜力 [30,31,59] 。如图 7 所示,西北工业大学梅辉等人 [60] 以陶瓷前驱体和热塑性树脂混合制备丝 材,通过 FDM 成形、热解、化学气相沉积等工艺制备了连续纤维增强 SiC 陶瓷材料构 件,致密化处理后的连续纤维增强 SiC 陶瓷强度可达 120.2 ± 4.5 MPa。 图 7 FDM 制备连续纤维增强 SiC [60] 。 (a) 连续纤维 FDM 成形工艺原理; (b) 连续 C f /SiC 蜂窝结构 Figure 7 Continuous fiber reinforced SiC prepared by FDM [60] . (a) Process principle of FDM forming continuous fiber; (b) Continuous Cf/SiC honeycomb structures 2.4 片材增材制造工艺 薄材叠层增材制造(LOM)是一种以片材为原料,通关激光切割二维截面,热压辊 涂敷粘结剂,层层叠加制备三维实体的增材制造工艺 [61,62] 。LOM 所使用的片材包括纸、 织物、陶瓷带材等 [63~65] 。2007 年,Windsheimer 等人 [66]…”
Section: 墨水直写(Diw)工艺unclassified
“…Table 1 shows some of the most important advantages and disadvantages of each printing manufacturing technology. Among them, extrusion‐type 3D printing, known as DIW, [ 14 ] offers the capability to lower cost and rapid assembly of arbitrary and stereoscopic 3D structures without additional auxiliary devices, such as masks or laser sources, [ 15 ] by incorporating a wide range of ink materials, such as ceramics, [ 16 ] polymers, [ 17 ] biomaterials, [ 18 ] and liquid metals. [ 19 ] During a typical extrusion‐based 3D printing process, ink filaments are continuously extruded through a nozzle, which is controllable through layer‐by‐layer building for well‐defined projects.…”
Section: Direct Ink Writing Techniquementioning
confidence: 99%